Economic Data Dissemination : What Influences Country Performanceon Frequency and Timiliness? - Agca, Mehmet (IMF Working Papers; Working Paper ;, 2001)
Despite initial improvements in macroeconomic data dissemination following the emerging markets crises of the late-1990s, large differences among countries remain. To identify the factors behind such differences, this paper develops measures of the frequency and timeliness of macroeconomic data dissemination for 180 countries. After discussing potential factors influencing data dissemination, the paper confirms the importance of a range of economic, social, and demographic factors. The relative importance of these factors in different regions is discussed, as well as the broader policy implications for strengthening macroeconomic data dissemination.